2005
DOI: 10.1016/j.progpolymsci.2005.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Neutron scattering investigations on methyl group dynamics in polymers

Abstract: Among the different dynamical processes that take place in polymers, methyl group rotation is perhaps the simplest one, since all the relevant interactions on the methyl group can be condensed in an effective mean-field one-dimensional potential. Recent experimental neutron scattering results have stimulated a new revival of the interest on methyl group dynamics in glasses and polymer systems. The existence of quantum rotational tunnelling of methyl groups in polymers was expected for a long time but only very… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
76
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 73 publications
(85 citation statements)
references
References 137 publications
(467 reference statements)
6
76
0
Order By: Relevance
“…This implies that the enhancement of conductivity is not due to an increased polymer mobility. The QENS spectra revealed a rotation in both filled and unfilled samples that would be consistent with rotation of (PEO) 6 :LiClO 4 , a channel-like structure that is more conductive than the amorphous equivalent. The authors suggested that the NP surface would stabilize the conductive (PEO) 6 :LiClO 4 structure, allowing them to persist long enough for conduction to occur.…”
Section: Nanocomposites Solid Polyelectrolytes and Blendsmentioning
confidence: 52%
See 2 more Smart Citations
“…This implies that the enhancement of conductivity is not due to an increased polymer mobility. The QENS spectra revealed a rotation in both filled and unfilled samples that would be consistent with rotation of (PEO) 6 :LiClO 4 , a channel-like structure that is more conductive than the amorphous equivalent. The authors suggested that the NP surface would stabilize the conductive (PEO) 6 :LiClO 4 structure, allowing them to persist long enough for conduction to occur.…”
Section: Nanocomposites Solid Polyelectrolytes and Blendsmentioning
confidence: 52%
“…The three main goals were (i) to study the local dynamics associated to small molecular groups (e.g., methyl groups, phenylene rings, etc; see, e.g., 22,[24][25][26][27] ), (ii) to characterize the dynamics at the interchain level, related to the structural relaxation in connection to the glass-transition phenomenon (see, e.g. ref.…”
Section: Recent Progress On Polymer Dynamics By Neutron Scatteringmentioning
confidence: 99%
See 1 more Smart Citation
“…This glass transition is also observed in some liquid alloys and one of the questions to be answered is the role of the alloy's composition in the glass transition. In many binary or ternary melts the cooling rate needed to vitrify the systems is in the order of 10 6 Ks -1 , while in alloys like Pd 43 Ni 10 Cu 27 P 20 cooling rates less than 0.1 Ks -1 are sufficient to bring the alloy into a glassy state [28]. For this special alloy it was found, that the self-diffusivity close to the liquidus temperature as measured by QENS is about one order of magnitude less than for simple metallic liquids at their melting temperature, while on the other hand the diffusivity is larger as compared to good metallic glass formers.…”
Section: Molten Metalsmentioning
confidence: 99%
“…Methyl group dynamics plays an important role in many polymer systems. In [43] this dynamical process is explained in great detail and provides a good starting point for the phenomenon of the so-called tunneling. In addition, the number of reports on experiments on micellar systems is increasing continuously.…”
Section: Polymersmentioning
confidence: 99%